A review of survivability and remedial actions of tidal current turbines - Chen, L.; Lam, Wei-Haur (Elsevier, 2015)
Tidal current energy is one of the most predictable ocean renewable energies. Survivability of the device used to harness tidal power and its remedial actions are critical to ensure a successful power generation. Marine environment is harsh with the continuous attacks of waves, current saline water and microorganism. Support structures are discussed including gravity base, monopile, tripod/piled jacket and floating structure. Extreme weather increases the wave height and current speed to produce high loading at the turbine. Support structure is designed to sustain the loadings from the extreme weather. Protective seabed unit should be included to prevent the seabed scouring. Corrosion reduces the strengths of rotor, support structure and nacelle. Penetration of sea water into nacelle may damage the generator. Scheduled examination is important to ensure water tight condition of nacelle. Marine fouling from microorganism needs the proper painting as protection. The study presents the survivability of tidal current turbine and suggests the remedial actions to protect the device. (C) 2014 Elsevier Ltd. All rights reserved.